2012
DOI: 10.1371/journal.pmed.1001353
|View full text |Cite
|
Sign up to set email alerts
|

Food Pricing Strategies, Population Diets, and Non-Communicable Disease: A Systematic Review of Simulation Studies

Abstract: A systematic review of simulation studies conducted by Helen Eyles and colleagues examines the association between food pricing strategies and food consumption and health and disease outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
187
1
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(209 citation statements)
references
References 55 publications
11
187
1
10
Order By: Relevance
“…Excessive consumption of sucrose from caloric soft drinks has been increasingly related to various health problems such as childhood obesity [26] and type 2 diabetes mellitus [27], which are strongly associated with the development of non-communicable chronic diseases. Based on this association, a recent study by Eyles et al [28] suggests that raising taxes on the sale of this type of drink and subsidizing the production of fruits and vegetables would be a potential strategy to promote beneficial changes in the dietary pattern of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive consumption of sucrose from caloric soft drinks has been increasingly related to various health problems such as childhood obesity [26] and type 2 diabetes mellitus [27], which are strongly associated with the development of non-communicable chronic diseases. Based on this association, a recent study by Eyles et al [28] suggests that raising taxes on the sale of this type of drink and subsidizing the production of fruits and vegetables would be a potential strategy to promote beneficial changes in the dietary pattern of the population.…”
Section: Discussionmentioning
confidence: 99%
“…The main arguments against farm policies playing a role are: (i) subsidies have a mixed effect on the prices and production outputs of various food items (33,34,36) ; (ii) the impacts on commodity prices offer savings to the food industry, but have little effect on food costs at retail and even less on those prices passed on to consumers (35) ; (iii) food consumption is relatively unresponsive to changes in market prices and so the very small food price changes induced by farm subsidies could not have had large effects on food consumption patterns (34) ; and (iv) food consumption has not previously changed markedly in response to policy-induced adjustments in relative prices (32) . However, ecological studies and public health commentaries suggest that farm policies do matter for health (12,13,(37)(38)(39) . Since agricultural policy changes in the 1970s (the origin for today's policies), food supplythe amount of energy available to the population -has increased from 9075 kJ (2169 kcal)/person per d in 1970 to 10 853 kJ (2594 kcal)/person per d in 2009 (40) , with the largest increase seen in refined grains (782 kJ (187 kcal)) and added fats and oils (703 kJ (168 kcal)).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is echoed in findings that dietary variety is significantly associated with caloric availability from staples, but more strongly associated with caloric availability from non-staples (Hoddinott and Yohannes 2002). Furthermore, interventions that have deflated fruit and vegetable prices generally have found that consumption increases (Powell et al 2009;Waterlander et al 2013;Eyles et al 2012;French 2003;An et al 2013). …”
Section: Affordabilitymentioning
confidence: 99%